The architecture of privacy preserving, distributed electronic health records system - Wilusz, Daniel; Rykowski, Jarogniew (Architektura chroniącego prywatność, rozproszonego systemu informacji o pacjencie, 2011)
Electronic health records systems raised a great deal of controversy. On the one hand, immediate access to detailed patient’s history improves medical procedures and may be even vital to patient’s life. On the other hand, patient’s health records usually contain very sensitive data which may be misused if not securely managed. The aim of this paper is to present architecture of an information system that preserves the privacy of patient’s data by means of cryptographic techniques as well as proper cooperation among system participants.The main principle of the proposal is the assumption that entities know nothing more than is indispensible to them in order to fulfil their tasks
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 259-269
Keywords: electronic health record; privacy protection; health information system